A Noninvasive Body Setup Method for Radiotherapy by Using a Multimodal Image Fusion Technique. (December 2017) - Zhang, Jie; Chen, Ying; Chen, Yunxia; Wang, Chenchen; Cai, Jing; Chu, Kaiyue; Jin, Jianhua; Ge, Yun; Huang, Xiaolin; Guan, Yue; Li, Weifeng
Purpose: To minimize the mismatch error between patient surface and immobilization system for tumor location by a noninvasive patient setup method. Materials and Methods: The method, based on a point set registration, proposes a shift for patient positioning by integrating information of the computed tomography scans and that of optical surface landmarks. An evaluation of the method included 3 areas: (1) a validation on a phantom by estimating 100 known mismatch errors between patient surface and immobilization system. (2) Five patients with pelvic tumors were considered. The tumor location errors of the method were measured using the difference between the proposal shift of cone-beam computed tomography and that of our method. (3) The collected setup data from the evaluation of patients were compared with the published performance data of other 2 similar systems. Results: The phantom verification results showed that the method was capable of estimating mismatch error between patient surface and immobilization system in a precision of <0.22 mm. For the pelvic tumor, the method had an average tumor location error of 1.303, 2.602, and 1.684 mm in left–right, anterior–posterior, and superior–inferior directions, respectively. The performance comparison with other 2 similar systems suggested that the method had a better positioning accuracy for pelvic tumor location. Conclusion: By effectively decreasing an interfraction uncertainty source (mismatch error between patient surface and immobilization system) in radiotherapy, the method can improve patient positioning precision for pelvic tumor.